Subtracted 3D CT Angiography for Evaluation of Internal Carotid Artery Aneurysms: Comparison with Conventional Digital Subtraction Angiography - Sakamoto, S.; Kiura, Y.; Shibukawa, M.; Ohba, S.; Arita, K.; Kurisu, K. (American Journal of Neuroradiology, 2006)
BACKGROUND AND PURPOSE: 3D computed tomographic angiography (3DCTA) has been used recently for the evaluation of intracerebral aneurysms, but it is difficult to use this technique to visualize aneurysms near the base of the skull because of the presence of bone. Subtracted 3DCTA could replace digital subtraction angiography (DSA) for evaluation of aneurysms near the base of the skull if the 2 methods were to give similar results. The aim of this study was to compare the evaluation of aneurysms of the internal carotid artery (ICA) near the base of the skull by subtracted 3DCTA and DSA.METHODS: CTA and DSA were obtained in 25 patients with unruptured aneurysms of the ICA. To create subtracted 3DCTA images, we used a volume subtraction (VS) method, wherein nonenhanced volume data are subtracted from enhanced volume data. CTA and DSA were reviewed by 2 neuroradiologists who performed the detection and characterization of aneurysms of the ICA by using 2D multiplanar reformatted (MPR) and VS- and nonsubtracted (NS)-3DCTA images with volume rendering techniques.RESULTS: DSA detected 29 aneurysms in the 25 patients. VS-3DCTA detected all 29 aneurysms in the 25 patients and was equivalent to DSA for evaluating their characteristics (location, size, and direction). NS-3DCTA detected 19 (1 cavernous, 4 ophthalmic, 1 superior hypophyseal, 7 posterior communicating, and 6 anterior choroidal artery) of these 29 aneurysms, but it could not characterize ophthalmic and superior hypophyseal artery aneurysms because they were only partly visible on NS-3DCTA because of bony structures. 2D-MPR images detected all but the small aneurysms (24 of 29 detected). VS-3DCTA and 2D-MPR could visualize all branching arteries (ophthalmic, posterior communicating, and anterior choroidal) detected by DSA, but NS-3DCTA could not visualize ophthalmic arteries because of the presence of bony structures.CONCLUSION: VS-3DCTA can be used as an alternative to DSA for preoperative examination of aneurysms near the skull base, where it provides equivalent identification and characterization.